Assessment of Industrial Modules to Design a Gfma Process for Cyanide Recovery Based on a Phenomenological Model - Romero-Figueroa, J (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
Cyanide recovery in the gold-mining industry is a crucial step in terms of the cost of operation. Currently, a process such as AVR (acidification, volatilization and recycling), based on packed towers for stripping and absorption stages, addresses this issue with high levels of investment and operational costs. Gas-filled membrane absorption (GFMA) emerges then as an attractive alternative because the stripping and absorption stages can be performed in a single stage, reducing associated investment and operational costs. Despite the advantages of this technology, applications at industrial scale are still emerging. A possible reason is the lack of clear scaling-up methodologies where experimental data can be taken to select the optimum industrial hollow-fiber membrane contactor module (HFMC). The present study proposes a methodology to select adequately between available industrial Liqui-CelTM modules to design a process under optimal operational conditions. The methodology is based on a phenomenological model developed for recovering cyanide by using the GFMA process. Simulation of the Liqui-CelTM industrial membrane modules employed to recover cyanide in the GFMA process, both in a batch arrangement with a feed-flow rate, and in the range 10-125 m3/h, showed that in terms of cyanide recovery there are no differences between the modules tested when they work at the same feed-flow rate. The design criteria to scale-up was determined: to ensure performance at different scales, the length of the transfer unit (HTU) should be kept at different capacities of HFMC modules that comprise the equipment characteristics (mass-transfer area, stream velocities, and mass-transfer coefficient values). Additionally, the number of commercial modules Liqui-CelTM required to treat 57 m3/h and 250 m3/h ensuring a cyanide recovery of 95% was also determined. Finally, the most profitable option (lower pressure drop and module cost) resulted in the use of the 14 × 40 Liqui-CelTM module. © 2018 by the authors.